Assesment of Healthy Housing Sanitation in Bengkuring Residence Area, North Sempaja Sub-Dictrict, Samarinda City - Nada, Nur Nazliyatun; Wardhani, Amelia Yunita; Khairunnisa, Nur Baiti; Ramadanti, Nadiyah Karin; Pusparini, Ryzkita; Hutabarat, Fiery Indra Christian; Rachmawati, Ayudhia (Universitas Mulawarman, 2025)
The home plays an important role as a place of protection and family development to create a healthy physical, mental, and social life. The condition of a clean home that meets health standards can reduce the risk of environmentally-based diseases. Healthy home criteria require the achievement of proper lighting, ventilation, clean water, and adequate sanitation facilities. This study aims to evaluate the sanitation conditions of housing and settlements and conduct an inspection of healthy home criteria in housing areas in Bengkuring. This research method is descriptive, using direct observation and interviews. The research sample consists of 30 households selected through purposive sampling. The results show that of the 30 homes inspected, 47% were categorized as unhealthy. Contributing factors include the location of the homes on swampland, the presence of waste dumps, the use of non-ideal building materials, and homeownership by individuals who are no longer productive. There is a need for more attention to lighting, wastewater disposal, air circulation, and natural light inside the house. Additionally, increasing public understanding and awareness is crucial to creating housing that meets health standards